{10-[(x-2010)*2-2]*2}/3-2=0
Răspunsuri la întrebare
Răspuns de
1
{10-[(x-2010)×2-2]×2}÷3=2
10-[(x-2010)×2-2]×2=6
10-[(x-2010)×2-2]=3
(x-2010)×2-2= -7
(x-2010)×2= -5
x-2010= -5÷2
x= (-5÷2)+2010
Sper ca iti este de folos.
10-[(x-2010)×2-2]×2=6
10-[(x-2010)×2-2]=3
(x-2010)×2-2= -7
(x-2010)×2= -5
x-2010= -5÷2
x= (-5÷2)+2010
Sper ca iti este de folos.
mihaalb:
multumesc mult
Alte întrebări interesante
Geografie,
8 ani în urmă
Engleza,
8 ani în urmă
Geografie,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă